Hubungan Hadis Nabi dengan Akal: Studi Kritis Terhadap Wacana Ilmiah - Sulhayani, Sulhayani (Al-Qarawiyyin: Jurnal Ilmu Ushuluddin, 2025)
If the authenticity of a hadith is uncertain and contradicts reason, then the hadith is considered weak. However, if a hadith is considered authentic by hadith scholars, two different theories have emerged among scholars. The first theory argues that a true hadith never contradicts reason. According to this view, sound and clear reason will never contradict a sound hadith. On the contrary, the second theory argues that a hadith of the Prophet is considered weak if it contradicts reason. This study uses analytical and library research methods, utilizing various scientific works including books, articles, and writings of Muslim scholars. The findings of this study indicate that when a hadith, which is narrated through a strong chain of narrators and whose sanad continues to the Prophet, cannot contradict reason. However, if a hadith contradicts common sense, then it can be a valid reason to question its authenticity and consider it weak. Through a comprehensive analysis of scientific discourse, this study provides a deeper understanding of the complex relationship between hadith and reason and how Islam values ​​reason. This underlines the importance of a rigorous authentication process, emphasizing the need to consider the reliability of the sanad of the hadith and the principles of intellectual reasoning when assessing the strength or weakness of a Prophetic hadith.